Non-infectious pulpal disorders in dental organs with occlusal trauma - Celia Elena Mendiburu Zavala; Salvador Medina -Peralta; Pedro Lugo -Ancona; Rubén Armando Cárdenas-Erosa; Josué Carrillo-Mendiburu; Ricardo Peñaloza-Cuevas; David Cortés-Carrillo (Editorial Ciencias Médicas, 2016)
Introduction: Occlusal trauma is defined as an alteration in the occlusal relationships of the masticatory system, which may lead to inflammation of the periodontal ligament, the dental pulp and sensitive soft tissues. Objective: Iidentify non-infectious pulpal disorders in dental organs with occlusal trauma of patients from a public hospital in Mérida, Yucatán. Methods: An observational analytical study was conducted at a public hospital in Mérida, Yucatán, Mexico (2014). The study universe was 156 dental organs of 82 patients aged 20 years and over with occlusal trauma in permanent teeth and some degree of non-infectious pulp tissue disorder, based on the classification of the American Academy of Endodontics. Patients were also included who presented caries, fractures, fissures, fillings, endodontic treatment, orthodontic treatment or dentoalveolar trauma. Convenience non-probability sampling was applied. Voluntary informed consent was obtained. Medical and dental records were examined. An evaluation was carried out of pain signs and symptoms. Thermal and electric pulp tests were performed, as well as palpation, percussion and diagnostic staining/transillumination. Occlusal testing was conducted using articulating paper. Periapical radiographs were examined and interpreted. Descriptive statistics were used. Result: There was no pain in 53 % of the dental organs studied. Radiographic alterations were present in 63 %; the most common were pulp nodes (25 %). Pulpitis was reversible in 37 % (n= 58), and the most frequent occlusal trauma was malocclusion (n= 49). In the 156 teeth studied, the most common clinical sign was enamel wear (n= 56). Conclusions: Non-infectious pulpal disorders were present in a large number of permanent teeth of patients with occlusal trauma.